Chemical Structure of Conductive Filaments in Tantalum Oxide Memristive Devices and Its Implications for the Formation Mechanism. (17th February 2022) - Heisig, Thomas; Lange, Kristof; Gutsche, Alexander; Goß, Kalle Thorben; Hambsch, Sebastian; Locatelli, Andrea; Menteş, Tevfik Onur; Genuzio, Francesca; Menzel, Stephan; Dittmann, Regina
Abstract: Resistive switching in metal oxides is believed to be caused by a temperature and electric field driven redistribution of oxygen vacancies within a nanometer sized conductive filament. Accordingly, gaining detailed information about the chemical composition of conductive filaments is of key importance for a comprehensive understanding of the switching process. In this work, spectromicroscopy is used to probe the electronic structure of conductive filaments in Ta2 O5 ‐based memristive devices. It is found that resistive switching leads to the formation of a conductive filament with an oxygen vacancy concentration of ≈20%. Spectroscopic insights provide detailed information about the chemical state of the tantalum cations and show that the filament is not composed of a metallic Ta 0 phase. As an extreme case, devices after an irreversible dielectric breakdown are investigated. These devices feature larger conductive channels with higher oxygen vacancy concentrations. Using the experimental data as input for finite element simulations, the role of thermodiffusion for the formation process of conductive filaments is revealed. It is demonstrated that thermodiffusion is not the dominating effect for the filament formation here but might play a role in accelerating the forming process, as well as in the stabilization of the filament. Abstract : Spectromicroscopy of memristive Ta2 O5 devices identifies a nanometer sized conductive filament with an oxygen vacancy concentration of ≈20%. Spectroscopic insight provides detailed information about the chemical state of the tantalum cations and show that the filament is not composed of a metallic Ta 0 phase. Finite element simulations reveal that thermodiffusion may play a role in accelerating the filament forming process, although it cannot be the origin of its formation.